Comparative Evaluation of Inception V3 and ResNet 50 for Pneumonia Prediction - Bokhare, Anuja; Metkewar, P.S.; Ruhela, Sonakshi; Avasthi, Madhav; Rather, Aafaq A.; Shaikh, Mohammad Shahnawaz; Bashir, Raeesa; Dar, Showkat A. (International Journal of Statistics in Medical Research, 2026)
Pneumonia is a fatal respiratory infection that has become the leading cause of death among many people across the world. Its widespread has grabbed great attention making it a major topic for research under various domains. Its severity has led to the development of systems that can predict whether a patient has chances of being diagnosed with pneumonia or not, this is also called as computer aided diagnosis. However, current study intends to identify an Artificial Neural Network (ANN) model that has been able to provide the highest accuracy when it comes to predicting this life-threatening condition. The prediction was initially done with Machine learning techniques but with the introduction of ANN, it was observed that there are models that provided higher accuracy than the ML models. This study investigates how the concept of deep learning which is a vital part of ANN makes use of one of its most efficient models including Inception V3 and ResNet 50 for the prediction of pneumonia and compare their performance to suggest a better solution to the problem. Results indicate that ResNet50 offers clinically meaningful improvements in sensitivity and specificity, supporting its role as a decision-support tool for early pneumonia detection.